"The college is so different from anything I have done". A study of the characteristics of Nottingham Recovery College. Issue 1 (8th April 2014) - McGregor, Jane; Repper, Julie; Brown, Helen
Abstract : Purpose: – This paper aims to describe the working of one of the first Recovery Colleges (RCs) and explore the defining characteristics. Design/methodology/approach: – This study explores the ways in which an educational approach contributes to the process of recovery as observed in the Nottingham Recovery College (NRC). A mixed-method research design was adopted, combining interviews, observation and visual methods as well as analysis of quantitative data. The process contributed to the continuing development of "fidelity criteria", or defining principles and key features, of the college. Findings: – The NRC demonstrates the possibilities of offering an alternative approach within mental health services; one which is educationally rather than therapeutically informed. The design and operation of the college is informed by educational principles in the creation and execution of the curriculum. This is critically developed through processes of co-production and co-facilitation by those with professional and lived experience, supported by policy development, rigorous documentation and the creation of a supportive, but challenging culture and environment. Students are offered very real opportunities for involvement, progression and leadership within and beyond the college. Research limitations/implications: – Whilst building on work on education in self-management, the RCs move beyond the transmission of information to create new relationships between mental health professionals and students (rather than "service users") – and through this, the relationship between students and their "condition" appears to be transformed. Early evidence suggests the NRC also provides a model of interaction that is distinct in educational terms. Practical implications: – There is significant interest nationally and internationally in the development and operation of RCs in England. RCs present a possibility of transformation in the lives of people with long-term mental health conditions, with outcomes such as greater confidence and hope for the future in addition to widening social networks and providing opportunities for progression. They are also important in the implementation of Recovery through organisational change and the remodelling of commissioning arrangements. Originality/value: – This is the first paper to be presented for publication specifically on the NRC. There is currently little published research on RCs. These are unique (and varying) organisations which are creating considerable interest nationally and internationally. An exploration of their defining characteristics will feed into subsequent larger-scale research.